PERANAN FIELD OFFICER PT VASHAM KOSA SEJAHTERA DALAM PROGRAM KEMITRAAN DENGAN PETANI JAGUNG DI KECAMATAN KETAPANG KABUPATEN LAMPUNG SELATAN - Imam Sugiharto Dermawan; Irwan Effendi; Kordiyana K Rangga (Lampung University, 2019)
This study aims to determine the partnership patterns that are applied and analyze the roles of facilitators in partnership programs, the relationship between the roles of the facilitators and the productivity of farmer partners, the relationship between production and income of farmer partners, and the differences in productivity and income of farmer partners of PT Vasham Kosa Sejahtera and non-partners. This location was chosen purposively with consideration that South Lampung Regency is the largest corn production center in Lampung Province and Ketapang District, where there are most partner farmers of PT Vasham Kosa Sejahtera in South Lampung Regency. Respondents were 50 partner farmers and 50 non-partner farmers. This research method uses a survey method, descriptive analysis and rank Spearman correlation test. The results showed that the partnership pattern that was established with partner corn farmers belonged to the pattern of Agribusiness Operational Cooperation (KOA). The role of Field Officers PT Vasham Kosa Sejahtera in the partnership program as a whole is quite a role. There is no significant relationship beetwen role of field officer and productivity of partner farmer corn farming. There is significant relationship between production and income of partner farmers corn farming. There is diferenece productivity of partner farmers and non-partner farmers corn farming and no difference between income of partner farmers and non-partner farmers corn farming.Key words: corn farming, facilitators, farmers, partnerships, rolesThis study aims to determine the partnership patterns that are applied and analyze the roles of facilitators in partnership programs, the relationship between the roles of the facilitators and the productivity of farmer partners, the relationship between production and income of farmer partners, and the differences in productivity and income of farmer partners of PT Vasham Kosa Sejahtera and non-partners. This location was chosen purposively with consideration that South Lampung Regency is the largest corn production center in Lampung Province and Ketapang District, where there are most partner farmers of PT Vasham Kosa Sejahtera in South Lampung Regency. Respondents were 50 partner farmers and 50 non-partner farmers. This research method uses a survey method, descriptive analysis and rank Spearman correlation test. The results showed that the partnership pattern that was established with partner corn farmers belonged to the pattern of Agribusiness Operational Cooperation (KOA). The role of Field Officers PT Vasham Kosa Sejahtera in the partnership program as a whole is quite a role. There is no significant relationship beetwen role of field officer and productivity of partner farmer corn farming. There is significant relationship between production and income of partner farmers corn farming. There is diferenece productivity of partner farmers and non-partner farmers corn farming and no difference between income of partner farmers and non-partner farmers corn farming. Key words: corn farming, facilitators, farmers, partnerships, roles